The Implementation of Cognitive Conflict Learning Strategy in Efforts to Reduce Heat Misconception in Junior High School Students - Heny Ekawati Haryono; Khafidhoh Nurul Aini; Achmad Samsudin; Parsaoran Siahaan (Universitas Muhammadiyah Makassar, 2020)
The most misconceptions in learning physics originate from the students themselves which include the students' initial concepts, associative and humanistic thinking, wrong intuition, the stages of students' cognitive development, and students' abilities. The purpose of this study was to determine the profile of heat misconception in junior high school students after learning by using the TGT cooperative learning model with cognitive conflict strategies. The research design used in this study is One group pre-test and post-test design. The data collection instrument was a misconception test in the form of a Three-tier Test totaling 20 questions. The results showed that before the treatment of the five junior high schools had an average percentage of misconceptions of 54.37%. After learning using the TGT cooperative learning model with cognitive conflict strategies the average percentage of students' misconceptions is 37.58%. Thus, there was a decrease in the percentage of misconceptions by 16.79%. The conclusion of this study is the TGT cooperative learning model with cognitive conflict strategies can reduce heat misconception in junior high school students in Lamongan District.